2016
DOI: 10.1108/jhom-01-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Management practices in Australian healthcare: can NSW public hospitals do better?

Abstract: Purpose – The purpose of this paper is to investigate the determinants of best management practices in an Australian state-run healthcare system, namely New South Wales (NSW), and studies the impact of a range of hospital factors in driving best management practices as a means of enhancing healthcare delivery. Design/methodology/approach – This study adapts a unique survey instrument globally tested to quantify the multi-dimensional natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…By contrast, Agarwal et al 40 found that the number of doctors serving on a hospital’s board of directors is unrelated to management performance because doctors are primarily responsible for clinical quality rather than hospital management. Thus, some researchers believe that board members concurrently serving as doctors and directors reduce the effectiveness of a hospital’s board of directors.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, Agarwal et al 40 found that the number of doctors serving on a hospital’s board of directors is unrelated to management performance because doctors are primarily responsible for clinical quality rather than hospital management. Thus, some researchers believe that board members concurrently serving as doctors and directors reduce the effectiveness of a hospital’s board of directors.…”
Section: Discussionmentioning
confidence: 95%
“…Five studies reported on medical leadership within organisations. 31 34 35 39 44 Konu and Viitanen 34 investigated the incidence of shared leadership among 433 middle-level managers (eg, chief doctors, nursing directors) in social service and healthcare in Finland. Quantitative analysis of survey data on leadership practices found that shared leadership practices were more common among managers without a medical background.…”
Section: Resultsmentioning
confidence: 99%
“…In other work, Agarwal et al 31 sought to determine whether there is a positive association between Management Practices Score (MPS) and the level of clinical education of managers in 42 Australian acute care public hospitals. The MPS for each hospital was calculated from interview responses of 116 managers to a survey of 21 hospital management practices across multiple dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…It aims to improve the service flow in hospitals but the overall quality care was compromised. Furthermore, Agarwal et al (2016) proposed a solution of best management practices to deliver quality health care services. However, it requires continuous changes in the organization as per the patient requirements, which is challenging and difficult to introduce.…”
Section: Framework Methods and Toolsmentioning
confidence: 99%